Lack of association between polymorphisms of the IL18R1 and IL18RAP genes and cardiovascular risk: the MORGAM Project - Nicaud Viviane; Cambien François; Kuulasmaa Kari; Salomaa Veikko; DeSuremain Maylis; Alanne Mervi; Proust Carole; Grisoni Marie-Lise; Wiklund Per-Gunnar; Virtamo Jarmo; Kee Frank; Tiret Laurence; et al. (BMC, 2009)
Abstract Background Interleukin-18 is a pro-inflammatory cytokine suspected to be associated with atherosclerosis and its complications. We had previously shown that one single nucleotide polymorphism (SNP) of the IL18 gene was associated with cardiovascular disease (CVD) through an interaction with smoking. As a further step for elucidating the contribution of the IL-18 pathway to the etiology of CVD, we here investigated the association between the genetic variability of two IL-18 receptor genes, IL18R1 and IL18RAP, with the risk of developing CVD. Methods Eleven tagging SNPs, 5 in IL18R1 and 6 in IL18RAP, characterizing the haplotypic variability of the corresponding genes; were genotyped in 5 European prospective CVD cohorts including 1416 cases and 1772 non-cases, as part of the MORGAM project. Both single-locus and haplotypes analyses were carried out to investigate the association of these SNPs with CVD. Results We did not find any significant differences in allele, genotype and haplotype frequencies between cases and non-cases for either of the two genes. Moreover, the search for interactions between SNPs located in different genes, including 5 IL18 SNPs previously studied in the MORGAM project, and between SNPs and environmental factors remained unfruitful. Conclusion Our analysis suggests that the variability of IL18R1 and IL18RAP genes are unlikely to contribute to modulate the risk of CVD.